Change Goals Robustly Predict Trait Growth: A Mega-Analysis of a Dozen Intensive Longitudinal Studies Examining Volitional Change. Issue 6 (August 2020) - Hudson, Nathan W.; Fraley, R. Chris; Chopik, William J.; Briley, Daniel A.
Research suggests that change goals (desires to change personality traits) predict subsequent trait growth. In this article, we (re)analyzed all data our labs have collected as of May 2019 that included measures of change goals and repeated measures of personality traits (12 studies; total n = 2, 238). Results indicated that change goals robustly predicted growth in all five traits. Effect sizes were largest for extraversion and emotional stability (people with high change goals were predicted to experience ∼0.16 SD s greater growth across 16 weeks than their peers with average goals) and smallest for agreeableness and openness (people with high change goals were predicted to experience ∼0.05 SD s greater growth across 16 weeks than their peers with average goals). Thus, our analyses reinforce that people change in ways that align with their desires across time.